The Distributional Impact of Social Transfers in the European Union: Evidence from the ECHP - Christopher Heady; Theodore Mitrakos; Panos Tsakloglou (Institute for the Study of Labor (IZA), 2001)
Social transfers vary enormously across the EU, as has been demonstrated in earlier research. This paper analyses the comparative effects of cash transfers on inequality and poverty, using consistent household data. The analysis shows that the distributional impact of these transfers is greater in countries that spend a higher proportion of income on them but that there are other important determinants, including the distribution of funds between different types of transfers and the degree of targeting for each transfer.
Keywords: I38; H55; 330; social transfers; income distribution; European Union; household survey; Sozialtransfer; Öffentliche Sozialausgaben; Wirtschaftspolitische Wirkungsanalyse; Einkommensverteilung; Armut; Schätzung; EU-Staaten